La guerra en el Cantar de los Nibelungos, analizada desde el trasfondo de la tradición cristiana y germánica - Jesús Pérez García (Futhark. Revista de Investigación y Cultura, 2021)
The Nibelungenlied is an epic poem that depicts violence in a very brutal way. From the Romantic point of view, this is consistent with an heroic bias which originated at the times of the great migrations. But it must be considered that the poem was composed with the background of the chivalry, and violence can not be interpreted in the same way as in the prehistoric Germanic ages. Actually, the vengeance that Kriemhild unleashes ends up losing its legitimacy. To understand the ideology towards violence (state-organised or private) it is necessary to take into account the Christian traditions (which evolved from an initial comprehensive prohibition) and the survival of old Germanic customs.